Projeto e análise do desempenho de uma matriz-protótipo para deformação plástica severa de metais por extrusão em canal angular com torção - Teixeira, Rafael Fernando (2023)
The emphasis of this work was to develop a prototype of a Twist Equal-Channel Angular Pressing die (T-ECAP). ECAP consists of pressing a metallic billet through two sequential channels with same cross-section area forming an angle, imposing large shear strains on the material without significant changes on their initial dimensions. In addition, it is widely studied due to its ability to produce ultrafine-grained materials (< 1 μm). T-ECAP has a twist zone in addition to the sequential channels, so that in each pass a combined shear strain is applied, increasing equivalent strain per pass. In this study, in an original die for T-ECAP, extrusions were made with Cu-0.7Cr-0.07Zr alloy and pure copper, which are very ductile at room temperature, for comparison with the results from numerical simulation obtained by finite element method in a Deform® software. The processed materials had their microstructure studied by metallography and strain distribution was evaluated by Vickers hardness mappings. Performance analysis of the T-ECAP die were also carried out with numerical simulations being performed with different combinations of geometries. The results indicated that in the original ECA-T die a single pass resulted in an equivalent strain of approximately 0.61, using the combination φ = 120° and Φ = 44° in the ECAP zone and ω = 45° and β = 23° in the twist zone. For T-ECAP die optimization, among analyzed combinations, the one that resulted in a smaller heterogeneity in the distribution of stresses and strains with a smaller pressing load was a die with φ = 120°, Φ = 22°, ω = 90° and β = 25°, imposing an average equivalent strain of 1.12 per pass. Thus, based on these findings, a mechanical design of a new T-ECAP prototype die was proposed.